1997
DOI: 10.1016/s0014-5793(97)00250-0
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and expression of pokeweed antiviral protein from seeds in Escherichia coli and its inhibition of protein synthesis in vitro

Abstract: Pokeweed antiviral proteins (PAP) represent a family of protein toxins isolated from various organs and at different stages of development of Phytolacca americana (pokeweed). We isolated, sequenced and characterized for the first time a complete cDNA encoding a pokeweed antiviral protein expressed in seeds. The cDNA of PAP-S consists of 1249 nucleotides and encodes a mature 262 amino acid protein. Its predicted amino acid sequence is more similar to PAP (76%) than to PAP II (31%). It is known from literature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…PAP-S1 and PAP-S2 were found to inhibit infection of HEp-2 cells by herpes simplex virus and poliovirus and also the replication of human immunodeficiency virus 1 (HIV-1) in isolated mononuclear blood cells infected in vitro. It was also found that PAP-S1 and PAP-S2 were more effective than other RIPs at inhibiting the expression of reverse transcriptase in infected cells [3]. It was also found in a recent study that PAP was efficient against Japanese encephalitis virus (same group, family and genus as Zika virus) [5].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…PAP-S1 and PAP-S2 were found to inhibit infection of HEp-2 cells by herpes simplex virus and poliovirus and also the replication of human immunodeficiency virus 1 (HIV-1) in isolated mononuclear blood cells infected in vitro. It was also found that PAP-S1 and PAP-S2 were more effective than other RIPs at inhibiting the expression of reverse transcriptase in infected cells [3]. It was also found in a recent study that PAP was efficient against Japanese encephalitis virus (same group, family and genus as Zika virus) [5].…”
Section: Introductionmentioning
confidence: 81%
“…Since only a partial cds of PAP-S1 (GenBank: AB071854.1) was available, different primers were designed based on the available mRNA PAP-S2 cds (GenBank: X98079.1) to sequence the complete cds of PAP-S1. The assumption that primers based on the mRNA of PAP-S2 would allow us to amplify PAP-S1 sequence was based on the fact that PAP-S1 and PAP-S2 are highly identical, and also on the previous speculation that PAP-S1 and PAP-S2 were simply two different forms of only one available pokeweed antiviral protein present in seeds, and thus in the same locus leading to similar mRNA [3]. The forward primer used was 5'-AGAAGCGGCAAAGGGAAGATGAA-3' and for the reverse primer was 5'-CCATTGGCCCGGCCTCTTATTT-3'.…”
Section: Pap-s1mentioning
confidence: 99%
“…The total inhibition is attained at 0.83nM for RTA/PAP-S1R68G while PAP-S1R68G barely reaches 90% at 16.67nM, possibly due to the single point mutation (R68G). It is also interesting to note that PAP-S1R68G has about the same IC50 as PAP-S2 (0.07) but a much higher total inhibition point (around 1.2nM for PAP-S2) [2]. These results not only show that RTA/PAP-S1R68G is at least twice as fast as PAP-S1R58G but also 16 times more potent.…”
Section: Production and Purification Of Recombinant Proteins In E Comentioning
confidence: 69%
“…PAP, PAP II, PAP-S1, PAP-S2, and PAP-R are the forms that appear in spring leaves, summer leaves, isoform S1 and S2 in seeds, and roots, respectively. The molecular weight ranges from 29 kDa for PAP to 30 kDa for PAP-S's [2]. PAP-S1 has been identified as the most effective in inhibiting protein synthesis in vitro [3].…”
Section: Introductionmentioning
confidence: 99%
“…PAP-I (or simply PAP), PAP-II and PAP-III are leaf isoforms that appear in spring, early summer and late summer respectively [13,22,[31][32][33][34][35], whereas PAP-S1 and PAP-S2 are isoforms isolated from seeds that exhibit the highest activity in vitro of all the isoforms [36][37][38]. A further isoform, α-PAP, is similar in sequence to PAP-S1, and essentially expressed in all organs of the plant [38,39]; it shares 74% identity with PAP.…”
Section: Ribosome Inactivating Proteins (Rips)mentioning
confidence: 99%